Shakespearean Drama in Miloš Pietor›S Work: Between Prologue and Epilogue - Sládeček Ján (Slovenské divadlo)
William Shakespeare’s work has a very specific place in Miloš Pietor’s professional biography: it starts at the beginning of the artist’s creative period and then again at the end of his professional life. The study is devoted to this part of the director’s work. It analyzes the plays Merry Wives of Windsor (P. Jilemnický Theatre, 1963), Hamlet (Nová scéna Theatre 1974), comedy Love’s Labour’s Lost) (Nová scéna Theatre 1976) and presents the directorial and dramaturgical concept of Pietor’s first production after November 1989, The Merchant of Venice (1991). His planned premiere at the Slovak National Theatre (Slovenské národné divadlo) did not take place; the work was cancelled due to the director’s tragic death.